EFFECTIVENESS OF ONLINE LEARNING MANAGEMENT WITH THE SOLE (SELF ORGANIZED LEARNING ENVIRONMENTS) MODEL DURING THE COVID-19 PANDEMIC - Titi Fibrilianthi Carolina; Imam Mawardi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The occurrence of the Covid-19 pandemic in 2020 has reshaped various orders of life, including the world of education. Changes and adaptations in education management are a must in responding to the challenges of Islamic education during the pandemic and era of technological disruption 4.0. Changes in teaching and learning activities in various educational institutions, both schools and madrasas, which were originally conventional learning, namely face-to-face in class, shifted to Learning from Home (BDR) in a network (online) with an online (direct) or offline (delayed) system. SMPIT Ihsanul Fikri Mungkid is one of the schools in Magelang Regency that also has to go through the process of changing teaching and learning activities. This study aims to determine the management of online learning and the effectiveness of online learning during the Covid-19 pandemic at SMPIT Ihsanul Fikri Mungkid. This research method uses qualitative research methods. The data collection from this research is in-depth interviews and documentation studies. The results showed a good implementation and effectiveness of online learning management with the SOLE (Self Organized Learning Environments) model at SMPIT Ihsanul Fikri Mungkid. Management of the use of technology, human resource management to the management of learning programs and other supporting programs are carried out in order to obtain effectiveness in the process and results of online learning.